Glycyrrhizin induces reactive oxygen species-dependent apoptosis and cell cycle arrest at G(0)/G(1) in HPV18(+) human cervical cancer HeLa cell line - KHAN, IMRAN; Farooqui, Arshi; Khan, Fahad; Khan, IMRAN; Ansari, Irfan A. (My University, 2018)
Cervical cancer is the fourth most common cancer among women worldwide and is a major cause of morbidity and mortality. High-risk Human Papilloma Virus (mostly type 16 & 18) infection is the primary risk factor for the development of cervical carcinoma. The quest for strong, safe and cost effective natural antiproliferative agents that could reduce cervical cancer have been focussed now a day. Recently, glycyrrhizin, a triterpene glycoside (saponin) from licorice (Glycyrrhiza glabra Linn.), has been shown to exhibit potent antiproliferative and anticancer properties in a few preliminary studies. However, potential of this compound in cervical cancer has not been elucidated yet. Therefore the objective of this study was to analyze the antiproliferative and apoptotic properties of glycyrrhizin in human cervical cancer HeLa cells. Our results showed that glycyrrhizin exposure significantly reduced the cell viability of HeLa cells with a concomitant increase in nuclear condensation and DNA fragmentation in a dose dependent manner. The intracellular ROS generation assay showed dose-related increment in ROS production induced by glycyrrhizin. Glycyrrhizin also induced apoptosis in cervical cancer cells by exerting mitochondrial depolarization. Cell cycle study showed that glycyrrhizin induced cell cycle arrest in G(0)/G1 phase of cell cycle in a dose dependent manner. Thus, this study confirms the efficacy of glycyrrhizin in cervical cancer cells which could be an adjunct in the better prevention and management of cervical cancer worldwide.